2017
DOI: 10.1097/j.pain.0000000000000935
|View full text |Cite
|
Sign up to set email alerts
|

Stratifying patients with peripheral neuropathic pain based on sensory profiles: algorithm and sample size recommendations

Abstract: Supplemental Digital Content is Available in the Text.Phenotype stratification of patients with peripheral neuropathic pain can be conducted with a novel algorithm based on sensory profiles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
154
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 176 publications
(164 citation statements)
references
References 45 publications
6
154
1
3
Order By: Relevance
“…Thus, there is an increasing recognition that "one size does not fit all," and rather than having an agnostic approach (ie, blindly trying different therapies until one works), we should consider better clinical phenotyping and targeted therapies. 97 However, superficial clinical phenotyping in relation to symptomatology has not been shown to improve the response to therapy. 98 More detailed phenotyping using QST has shown that patients with an irritable nociceptor (IN) phenotype (n ¼ 31) compared to a non-IN phenotype (n ¼ 52) had a significantly greater response to oxcarbazepine and a reduced overall number needed to treat (NNT) (6.9 vs 3.9).…”
Section: Symptomatic Treatment Of Dpnmentioning
confidence: 99%
“…Thus, there is an increasing recognition that "one size does not fit all," and rather than having an agnostic approach (ie, blindly trying different therapies until one works), we should consider better clinical phenotyping and targeted therapies. 97 However, superficial clinical phenotyping in relation to symptomatology has not been shown to improve the response to therapy. 98 More detailed phenotyping using QST has shown that patients with an irritable nociceptor (IN) phenotype (n ¼ 31) compared to a non-IN phenotype (n ¼ 52) had a significantly greater response to oxcarbazepine and a reduced overall number needed to treat (NNT) (6.9 vs 3.9).…”
Section: Symptomatic Treatment Of Dpnmentioning
confidence: 99%
“…It is important to note that the pain part of a neuropathic problem has to be established using other pieces of the diagnostic armamentarium in addition. Additional diagnostic assessments, including quantitative sensory testing 47 , corneal confocal microscopy 48 and skin biopsy 49 , may be helpful for the clinician to diagnose the presence of a neuropathic pain component in rare but challenging cases (e.g. small-fibre neuropathy).…”
Section: We Do Not Know How To Screen For and Diagnose Mixed Pain Defmentioning
confidence: 99%
“…Currently there is a growing interest in characterizing the somatosensory profile of patients with chronic pain using both validated questionnaires and quantitative sensory testing (QST) . This may not only allow us to subgroup patients based on underlying mechanisms but also helps us to identify suitable targets for treatment and perhaps might help us differentiate responders from non‐responders .…”
Section: Introductionmentioning
confidence: 99%